WORKERS, PRODUCERS AND THE CREATIVE EXPERIENCE - Itani, Alice [UNESP]; Rei, Fernando (Assoc Brasileira Engenharia Producao-abepro, 2018)
Creative activities assume a measure of importance within what is known as the creative economy. Little is known, however, about the challenges and prospects that present themselves to those who work in those activities that are considered to be creative. The objective of this paper is to analyze workers' experiences, especially in individual projects. Statements were taken from workers who have already worked in companies. The experiences of these workers were analyzed on the basis of what they express in relation to the items: their relationship with the activity, the product, or the result of the work; their relationship with the time and value of the work; their understanding of creation; their possibility for creating; their mastery of the work process; and their understanding of the work process. It was found that the women in the cases chosen are highly trained for developing their particular activity and have a relationship with it that is highly positive. They recognize that their activity is of value to society. The value of the work, however, is related to the time spent on the activity, which has not been remunerated for a long time. There are challenges for those who depend on the time taken to sell the product, a process that is carried out with little support. Everyone masters and understands the work process undertaken in the activity, and they identify the product, or the result of their work. They realize that there are many possibilities for creation. Even when an idea has been developed before, there is the possibility of innovating.
Keywords: creative economy; creative experience; creative activities; work experience in creative activities; producers